Analisis Produksi Emping Melinjo dan Hubungannya dengan Pendapatan Pengrajin di Kecamatan Kumpeh Ulu Kabupaten Muaro Jambi - Rudi Hartawan; Adilla Adistya (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2026)
Melinjo chips are an important home industry in the Kumpeh Ulu District. This study aims to identify the factors that influence melinjo chip production, examine the relationship between melinjo chip production and the income of craftsmen, and assess the impact of government guidance on the development of melinjo chip production. The data used in this study are from a survey. The analysis method used in this study is descriptive and quantitative. The results of the study indicate that the variables of raw materials, labor, experience in making emping, capital, and guidance have a very significant effect on melinjo chips production. Partially, the raw materials and labor variables have a very significant effect at the 1% level on melinjo chips production. Meanwhile, the experience variable has no significant effect. There is a close relationship between production and the income of melinjo chips craftsmen, with a person correlation value of 0.99 (perfect). Guidance has a significant effect on the quality and quantity of melinjo chips production. Statistically, the F-value is 2.418 with a significance of 0.026 (<0.05). The t-value of the two-sided test was -2.42, which was significantly different with a significance level of 0.019 (<0.05).